Running the Risk - Examining Dermatologic Concerns and Skin Neoplasms in Runners - Partyka, Alicja; Wierzejska, Natalia; Nowak, Agnieszka; Fugas, Agnieszka; Smykiewicz, Karolina; Dobrzańska, Justyna; Pach, Magdalena; Chmielowiec, Zuzanna; Dziedzic, Mariola; Michalczewska, Aneta (Quality in Sport, 2024)
This review summarizes the most prevalent dermatologic conditions encountered by runners and provides evidence-based recommendations for prevention and management. Due to high levels of ultraviolet radiation exposure, friction forces, specific environment of the activity and used garment runners are at the risk of various dermatologic complications, including skin neoplasms. Sun protection measures, such as applying sunscreen with sufficient SPF, wearing photoprotective clothing, and avoiding peak sun hours, are crucial for mitigating this risk. Friction-related injuries like blisters, calluses, and jogger's nipples are common among runners and can be prevented through proper footwear, moisture management, and lubrication. Educational interventions promoting safety practices are necessary to raise awareness and encourage behavioural change among runners.